Akibat Hukum Bagi Notaris Atas Pembuatan Akta Pengalihan Merek yang Belum Terdaftar - Merine Harie Saputri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Transfer of rights is a legal event in which the ownership rights of one party are transferred to another party preceded by certain conditions or agreements justified by law. Marks as assets in the form of intangible objects can be transferred according to the provisions of Article 41 paragraph 1 Law number 20 of 2016 concerning Marks and Geographical Indications. There are additional arrangements regarding the process of transferring rights contained in the provisions of article 41 paragraph 8, namely the transfer of rights to a mark can be carried out at the time of application for a mark. As is well known, marks that are still being applied for at the Directorate of Marks and Geographical Indications may not necessarily be registered in the General Register of Marks, so that applications for marks being transferred do not yet have a strong basis of rights as the object of the transfer agreement. Notary is a position that is given the authority to make an authentic deed. Based on article 1 number (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Offices Of course, with this authority, the Notary Office is expected to be able to fulfill the interests of the appearers to realize their interests stated in the deed, especially making agreements trademark transfer that is still being applied for. In this study, the authors focus on the validity of the trademark transfer agreement that is still being applied for and the legal consequences for the notary who makes the agreement if the applied mark cannot be registered in the General Register of Marks based on the trademark laws and regulations on the position of notary public and other applicable laws. interrelated and based on research conducted by the authors.